A comparison of levels of proficiency in English between primary fiv e pupils initially taught in English and those initially taught in vern aculars' in Masindi district - Wandera, Gerard Majella (Kampala : Makerere University, 1993)
Thesis (M.Ed.) - Makerere University, 1993.
Includes bibliographical references (p. 69-73).
Keywords: English language -- Study and teaching (Elementary) -- Uganda -- Mas indi district